Can antipsychotic dose reduction lead to better functional recovery in first‐episode psychosis? A randomized controlled‐trial of antipsychotic dose reduction. The reduce trial: Study protocol. Issue 6 (29th November 2018) - Weller, Amber; Gleeson, John; Alvarez‐Jimenez, Mario; McGorry, Patrick; Nelson, Barnaby; Allott, Kelly; Bendall, Sarah; Bartholomeusz, Cali; Koval, Peter; Harrigan, Susy; O'Donoghue, Brian; Fornito, Alex; et al.
Abstract : Antipsychotic medication has been the mainstay of treatment for psychotic illnesses for over 60 years. This has been associated with improvements in positive psychotic symptoms and a reduction in relapse rates. However, there has been little improvement in functional outcomes for people with psychosis. At the same time there is increasing evidence that medications contribute to life shortening metabolic and cardiovascular illnesses. There is also uncertainty as to the role played by antipsychotic medication in brain volume changes. Aim: The primary aim of the study is, in a population of young people with first‐episode psychosis, to compare functional outcomes between an antipsychotic dose reduction strategy with evidence‐based intensive recovery treatment (EBIRT) group (DRS+) and an antipsychotic maintenance treatment with EBIRT group (AMTx+) at 24‐months follow‐up. Methods: Our single‐blind randomized controlled trial, within a specialist early psychosis treatment setting, will test the whether the DRS+ group leads to better vocational and social recovery than, the AMTx+ group over a 2‐year period in 180 remitted first‐episode psychosis patients. Additionally, we will examine the effect of DRS+ vs AMTx+ on physical health, brain volume and cognitive functioning. This study will also determine whether the group receiving DRS+ will be no worse off in terms of psychotic relapses over 2 years follow‐up. Results: This paper presents the protocol, rationale and hypotheses for this study which commenced recruitment in July 2017. Conclusion: This study will provide evidence as to whether an antipsychotic dose‐reduction recovery treatment leads to improved functioning and safer outcomes in first‐episode psychosis patients. In addition, it will be the first‐controlled experiment of the effect of exposure to antipsychotic maintenance treatment on brain volume changes in this population.